2022
DOI: 10.3390/ijms23169134
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Mitigated Obesity-Driven Cancer Aggressiveness in Tumor-Bearing Mice

Abstract: Metformin may offer benefits to certain cancer populations experiencing metabolic abnormalities. To extend the anticancer studies of metformin, a tumor model was established through the implantation of murine Lewis Lung Carcinoma (LLC) cells to Normal Diet (ND)-fed and High-Fat Diet (HFD)-fed C57BL/6 mice. The HFD-fed mice displayed metabolic and pro-inflammatory alterations together with accompanying aggressive tumor growth. Metformin mitigated tumor growth in HFD-fed mice, paralleled by reductions in circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Studies have demonstrated that metformin decreases NET production, even in the presence of NET stimulants and recent evidence in hepatocellular carcinoma and pancreatic cancer confirmed that metformin reduced the production of NETs and the metastatic potential of these two cancers [ 246 , 247 , 248 ]. This has subsequently been corroborated in preclinical animal models [ 249 ].…”
Section: Emerging Therapeutic Strategiesmentioning
confidence: 78%
“…Studies have demonstrated that metformin decreases NET production, even in the presence of NET stimulants and recent evidence in hepatocellular carcinoma and pancreatic cancer confirmed that metformin reduced the production of NETs and the metastatic potential of these two cancers [ 246 , 247 , 248 ]. This has subsequently been corroborated in preclinical animal models [ 249 ].…”
Section: Emerging Therapeutic Strategiesmentioning
confidence: 78%
“…New evidence in hepatocellular carcinoma (HCC) and pancreatic cancer (PC) demonstrated that metformin attenuated NET production and reduced the metastatic potential of HCC and PC cells [253,254]. The role of metformin in attenuating NET-mediated carcinogenesis was corroborated in further murine models [255]. Interestingly, a recent presentation at AACR's Annual Meeting revealed that patients with type 2 diabetes mellitus suffering from colorectal cancer had significantly improved DFS in the presence of metformin, with tissue analysis identifying a significant reduction in tumor-associated NETs and a significant increase in CD8 + T-cells.…”
Section: Repurposed Compounds Facilitating Net Prevention or Modulati...mentioning
confidence: 92%
“…In addition, HMGB1 was identified as a facilitator molecule that promotes the transition process to NETS. These results suggest that metformin plays a role in obesity-induced cancer aggressiveness by inhibiting HMGB1-induced NET formation and may be a potential target drug ( Chen et al, 2022b ).…”
Section: Potential Targeted Drugsmentioning
confidence: 95%